Correlates of HPV: a cross-sectional study in women with normal cytology in north-central Morocco - Bahia Bennani; Sanae Bennis; Chakib Nejjari; L'Houcine Ouafik; Moulay Abdelilah Melhouf; Karima El Rhazi; Kaoutar Znati; Hikmat Chaara; Chahrazed Bouchikhi; Afaf Amarti Riffi (Journal of Infection in Developing Countries)
Introduction: Epidemiological studies have shown the association between risk of developing cervical cancer and the persistence of high-risk papillomavirus types in addition to some co-factors. However, little is known about co-factors associated with human papillomavirus (HPV) infection, especially in developing countries. This study aims to determine HPV status and associated risk factors in women with normal cytology living in the north-central area of Morocco.